Penerapan Algoritma C4.5 Untuk Mengukur Tingkat Kepuasan Mahasiswa - Riandari, Fristi; Simangunsong, Agustina (Pelita Nusantara Medan, 2019)
Measuring student satisfaction is very important to note given the high level of competition in the education world as knowledge and technology develops. In measuring student satisfaction it is very important to consider whether the services expected by students are in accordance with what is received. Measuring student satisfaction will greatly help a university in improving the quality of service which will also have an impact on increasing the number of students. The system that is needed is the Application of Data Mining in Measuring Student Satisfaction. Where students will be objects that provide an assessment / opinion on variables that have characteristics, namely Tangiable, Reability, Responsivnes, Assurance, Empathy. This system was built with the C4.5 algorithm and Testing system with RapidMiner 7.5 application rocks